2020
DOI: 10.1038/s41598-020-60672-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived small intestinal myofibroblasts direct perfused, physiologically responsive capillary development in a microfluidic Gut-on-a-Chip Model

Abstract: The development and physiologic role of small intestine (SI) vasculature is poorly studied. This is partly due to a lack of targetable, organ-specific markers for in vivo studies of two critical tissue components: endothelium and stroma. This challenge is exacerbated by limitations of traditional cell culture techniques, which fail to recapitulate mechanobiologic stimuli known to affect vessel development. Here, we construct and characterize a 3D in vitro microfluidic model that supports the growth of patient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…We have shown that patient-derived ISEMFs have angiogenic properties and form a vascular network when co-cultured with ECs in microfluidic devices. Additionally, we have shown that inhibition with Erlotinib, a receptor tyrosine kinase inhibitor of EGFR, prevents vasculogenesis in these co-cultures [44]. Given these prior findings, and the fact that we have shown that EGFR was strongly expressed in ISEMFs, we used this ex vivo microfluidic model of human small intestine to study the effects of EGFR signaling from ISEMFs on ECs.…”
Section: Plos Onementioning
confidence: 98%
See 4 more Smart Citations
“…We have shown that patient-derived ISEMFs have angiogenic properties and form a vascular network when co-cultured with ECs in microfluidic devices. Additionally, we have shown that inhibition with Erlotinib, a receptor tyrosine kinase inhibitor of EGFR, prevents vasculogenesis in these co-cultures [44]. Given these prior findings, and the fact that we have shown that EGFR was strongly expressed in ISEMFs, we used this ex vivo microfluidic model of human small intestine to study the effects of EGFR signaling from ISEMFs on ECs.…”
Section: Plos Onementioning
confidence: 98%
“…Media was changed daily. It has been previously confirmed that ECs alone do not form perfused capillary networks in the microfluidic device and that ISEMFs are part of the capillary network scaffolding [45]. All cultures were performed in a 5% oxygen, 5% CO2 incubator.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations